Product digitization and differentiation strategy change: Evidence from the book publishing industry - Miller, Cameron D.; Wang, Richard D. (Strategic Management Journal, 2024)
Abstract Research Summary We study product digitization as an impetus for firm strategy change. Product digitization can erode a firm's ability to differentiate through physical product attributes and prompts them to increase emphasis on nonphysical product attributes to sustain their competitive advantage. We expect this effect is pronounced among firms that have pursued a physical differentiation strategy prior to the digital age. However, we expect that countervailing forces exist such that the internal supply cost of and the external market demand for the nonphysical differentiator mitigate this effect. Evidence from publishers in the Amazon Kindle e‐book ecosystem supports our hypotheses. This study bridges the growing digital strategy literature and the classical competitive strategy literature. We discuss how our findings are relevant to a range of industries. Managerial Summary Many companies invest in superior physical product attributes to increase a customer's willingness‐to‐pay and entice purchase. However, when products become digitized—such as music streaming displacing CDs or e‐books replacing printed books—the effectiveness of physical product differentiation is diminished. We examine how book publishers manage this challenge at the advent of Amazon's Kindle e‐book technology. We find that publishers that have emphasized physical product attributes turn to emphasizing nonphysical product differentiation, namely, through offering more content. Yet, the extent of the strategy change is limited by the internal development cost of and the external demand for the nonphysical differentiator. We discuss how our findings are relevant to a range of settings, including both product and service companies.